Curbing bribe-giving in Malaysia: the role of attitudes and parents - Lim, Mengzhen; Yongchy, Sin; Wan Jaafar, Wan Munira; Mohd Khir, Azlina; Hamsan, Hanina H.; Min, Hooi Yong; Shin, Ling Wu; Pei, Boon Ooi; Lai, Derek Teik Ong; Chu, Sun Ong (Routledge, 2022)
One of the main challenges developing nations face is curbing bribery. While there are many efforts to curb bribery, most focused at macro level, such as law, while little has been examined at the micro level, e.g., individual behavior and intention. Those who did investigate at the micro level tend to focus on the recipients rather than the ones giving the bribe. We explored eight factors that influence Malaysian young adults’ bribe giving intention based on the Reasoned Action Approach (RAA). A total of 345 respondents (Mage = 20.68, SD = 2.01, 189 are females) completed questionnaires about all RAA variables. Partial Least Squares Structural Equation Modelling (PLS-SEM) was carried out using smartPLS3.0 to analyze the result. The result revealed that out of the eight variables, four variables—Instrumental attitudes, Experiential Attitudes, Parents’ descriptive norms and Capacity—explain 74% of the variance in bribe giving intention. An important take-away is that young adult’s perception of whether their parents gave or did not give bribes in a given situation is important in influencing their bribe giving intention. Bribe giving prevention messages must be targeted explicitly toward parents, where they play a crucial role in curbing this dishonesty.